VISIT THE BITING SITE IN LUMAJANG DISTRICT TO IMPROVE YOUR UNDERSTANDING OF ANCIENT INDONESIAN HISTORY: KUNJUNGI SITUS MENGGIGIT DI DISTRIK LUMAJANG UNTUK MENINGKATKAN PEMAHAMAN ANDA TENTANG SEJARAH INDONESIA KUNO - Rinna Rohmawati (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This writing aims to increase understanding of ancient Indonesian history, especially the Lamajang Tigang Juru Kingdom located in Lumajang, East Java, as a form of occupation that was the same era as the Majapahit Kingdom located in Trowulan, Mojokerjo. The big hope is that after understanding ancient history, we will grow in love and have a sense of pride in our country, Indonesia, which has been great since ancient times, the era of kingdoms with Hinduism and Buddhism, so that we will have a strong sense of nationalism because of its great history in the past. Indonesian historical events starting from prehistoric times, the Hindu Buddhist era or kingdoms, the era of colonialism to independence and reform until today. The history of Indonesia is uniquely beautiful and enchanting, so that the country of Indonesia is multicultural, consisting of various religions, traditions, customs and uniqueness. This is firmly engraved in a frame of diversity "unity in diversity with one Pancasila ideology". The research method used is a literature review which is applied to research in the course of Indonesian history during the Hindu-Buddhist period. Apart from that, this research uses an anthropological approach, while the theories used are evolutionism theory and functionalism theory. This research also uses historical research methods consisting of heuristics, criticism, interpretation and historiography. The results of this research are to discuss the historicity of the Biting site, its relevance to history learning and its use as a source of history learning. In the Biting Site, the Majapahit cultural heritage contains potential that can be used as a learning resource.